Development of research-based teaching materials to increase independent learning for students majoring in Indonesian language and literature - Yuhdi, Achmad; Lubis, Fitriani; Rosmaini, Rosmaini (STKIP Singkawang, 2024)
This research aims to develop research-based teaching materials to increase independent learning for students majoring in Indonesian language and literature. In this research, the development model used as a reference is using the 4D model. The 4D model is a learning device development model and an abbreviation for Define, Design, Development and Disseminate developed by Thiagarajan (1974). Based on the results of the feasibility test assessment that was carried out on research-based teaching materials, an assessment of the feasibility of the material was 88.98%, the feasibility of the media was 85.46%, and the student response test was 90.5%. The three of them got an average score of 88.31%. So, based on the percentage obtained by the three, the research-based teaching materials developed have met the requirements and received the status of appropriate teaching materials to be used as teaching materials for courses in writing scientific articles and publications in the Indonesian Language and Literature Education Study Program. An assessment of the student article writing component was obtained with an overall average score of 81.17 in the